2017
DOI: 10.5114/hpr.2017.67853
|View full text |Cite
|
Sign up to set email alerts
|

Actor and partner effects of coping on adjustment in couples undergoing assisted reproduction treatment

Abstract: health psychology report • volume 5(4), 7 original article background Infertility is a shared experience as it affects both partners. However, mutual dependencies between coping and adjustment at the couple level remain to be fully elucidated. The study attempted to address this issue using the Actor-Partner Interdependence Model (APIM) to examine the actor effect (the extent to which an individual's score on coping predicted their own level of depressive symptoms and life purpose) and the partner effect (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…In particular, daily instrumental and positive emotion-focused coping with patient's health condition predicted only an increase in daily positive affect, while daily CSE and negative emotionfocused coping predicted changes in both affect valences. The direction of these findings is consistent with our expectations and the current studies (Boyer et al, 2017;Fagundes et al, 2012;Kraemer et al, 2011;Kroemeke & Kubicka, 2017;Lafaye et al, 2014;Schokker et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In particular, daily instrumental and positive emotion-focused coping with patient's health condition predicted only an increase in daily positive affect, while daily CSE and negative emotionfocused coping predicted changes in both affect valences. The direction of these findings is consistent with our expectations and the current studies (Boyer et al, 2017;Fagundes et al, 2012;Kraemer et al, 2011;Kroemeke & Kubicka, 2017;Lafaye et al, 2014;Schokker et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…Studies have used APIM more often to examine the relationship between coping and its outcomes within dyads. Some cross-sectional (Gilbar, Weinberg, & Gil, 2012;Kroemeke & Kubicka, 2017;Meuwly, Bodenmann, & Coyne, 2012), longitudinal (Kraemer, Stanton, Meyerowitz, Rowland, & Ganz, 2011;Lafaye et al, 2014), and daily diary studies (Fagundes, Berg, & Wiebe, 2012) have shown significant actor and partner coping effects on wellbeing (e.g., anxiety, depressive symptoms, negative affect, post-traumatic stress symptoms, and life purpose). These results suggest that the beneficial effect produced by the so-called adaptive coping strategies (instrumental strategies) and the detrimental effect associated with maladaptive strategies (avoidance-or emotion-focused strategies) may crossover between dyad members, however, with some exceptions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some people treated for infertility also undergo assisted reproduction procedures, e.g., in vitro , which is a source of stress and elevated anxiety or even depression (Olivius et al, 2004 ). It is an experience, which requires additional coping efforts from the individual experiencing the treatment (Kroemeke and Kubicka, 2017 ).…”
mentioning
confidence: 99%